Correlation Between Learning Activities and Student Learning Outcomes Using Problem-Based Learning at SMAN Mojoagung Jombang: Korelasi Antara Aktivitas Belajar Terhadap Hasil Belajar Siswa Menggunakan Problem Based Learning di SMAN Mojoagung Jombang - Fatikhatun Nikmatus Sholihah; Moch Faizul Huda; Muhamad Zainal Dwi Wahyudi; Afif Rifqi (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2025)
This study aims to analyze the relationship between student activities in learning and cognitive learning outcomes. The method used in this research is a quantitative method with a correlational design. The population in this study were junior high school students, with a sample of class X-5 SMA Negeri Mojoagung Jombang using purposive sampling technique. Data was collected through observation of student activities and cognitive learning outcome tests. The results of the analysis show that there is a positive correlation between student activity and learning outcomes. This is indicated by a Pearson Correlation of 0.536 (moderate relationship) with a p-value of 0.001 which is smaller than 0.05, indicating a significant relationship. The Spearman Correlation is 0.578, which also shows a moderate but slightly stronger relationship. Since the correlation value between student activity and learning outcomes is within the range of 0.40 - 0.599, the relationship that occurs is in the moderate category. This means there is a relationship between student activity and learning outcomes. The implication of this research shows that increasing student involvement in the learning process can contribute to improving student learning outcomes